Penerapan Media Pembelajaran Interaktif Berbasis Aplikasi Bio Smart Materi Sistem Peredaran Darah Manusia Untuk Meningkatkan Hasil Belajar Siswa - Sherly Safitri; Beni Setiawan (UNIB Press, 2022)
The aim of this research was to describe improvement of student learning outcomes through implementation of interactive learning media based on Bio Smart application on human circulatory system material. The research design used was one-group pretest-posttest design. Samples of this research were students on second grade of junior high school 42 Surabaya two classes, namely VIII G and VIII H as replication class involving 56 students. Data collection techniques were observation, tests, and questionnaires. Research instruments were observation sheets on implementation of learning, test question sheets, and student response questionnaires. Data analysis carried out was analysis of implementation of learning, analysis of student learning outcomes, and analysis of student response questionnaires. Learning outcomes on pretest and posttest were analyzed by Statistical Package for the Social Sciences or SPSS version 26. Analysis contain normality test, homogeneity test, paired t-test, and independent t-test. Moreover, to describe increasing learning outcomes, N-Gain analysis is used. Result of this research is implementation of learning in both classes got results in Very Good category. Student learning outcomes have increased that there was significant difference between results of pretest and posttest in each class. In class VIII G there were 60.71% of students get N-Gain score in the High category. In class VIII H there were 57.14% of students get N-Gain score in High category. Responses given by students to learning from both classes get positive response in Very Good category. Conclusion obtained is implementation of interactive learning media based on Bio Smart applications can improve student learning outcomes.